Hubungan Perdarahan Antepartum Dengan Asfiksia Neonaturum Di RSUD ARIFN ACHMAD PROPINSI RIAU - Yanti, Juli Selvi (Jurnal Martenity and Neonatal, 2017)
Neonatal asphyxia is a condition in which a newborn who can not bemafas spontaneously and regularly within 1 minute after birth. Asphyxia included in the 15 largest disease cause of infant mortality in the Arifin Achmad Riau Province in 2014. This study aims to determine the relationship of the factors related to the occurrence of neonatal asphyxia Arifin Achmad Hospital in Riau Province in 2014. This research method using a quantitative analytical research type and design of case control. The population in this study were 72 respondents, the sampling technique is simple rondom sampling. Computerized data processing and data analysis was done by bivariate. The result showed that out of 72 respondents note that 36 respondents were asphyxia (50%) and does not occur asphyxia 36 respondents (50%), and women who experienced antepartum haemorrhage 43 respondents (59.7%) of the results of chi-square test of the relationship between antepartum haemorrhage with asphyxia neonaturum obtained value p = 0,016) with OR 3.750. It was concluded that there was statistically significant relationship between antepartum haemorrhage with asphyxia neonaturum. Pregnant women are advised to check the pregnancy more often minimal 4kali, to prevent the risk of pregnancy.